Diagnostic inference in performance evaluation: effects of cause and event covariation and similarity* - BROWN, CLIFTON (Contemporary Accounting Research, 1987)
This study experimentally tests some implications of psychological diagnostic inference theories and begins to extend these theories into a performance evaluation context. Subjects, who were required to assume the role of a manufacturing division manager, were asked to estimate the likelihoods of four potential causes of an assembly department's labor efficiency variance. The subjects were asked to reevaluate their causal likelihoods following: 1) evidence concerning the magnitude of the labor variance and the deviations of the four potential causes from their normal levels (similarity evidence) and 2) evidence concerning the covariation of a potential cause, and labor efficiency variances over the past five years (covariation evidence). The results generally confirmed a set of hypotheses predicting the effects of cause/event similarity and covariation upon individuals' causal inferences. Implications of these results for accounting information systems design are discussed in a concluding section. Résumé. Cette étude teste, au moyen d'une expérience, quelques‐unes des conclusions des théories d'inférence diagnostique psychologique et amorce l'application de ces théories dans un contexte d'évaluation de la performance. Les sujets, qui devaient assumer le rôle de directeur d'une division de fabrication, ont été invités à estimer les probabilités de quatre causes possibles de l'écart de rendement sur main‐d'œuvre d'un atelier d'assemblage. Les sujets furent invités à réévaluer leurs probabilités causales selon: 1) des informations relatives à l'ampleur de l'écart sur main‐d'œuvre et à la dispersion des quatre causes potentielles par rapport à leur niveau normal (preuve de similitude) et 2) des informations relatives à la co‐variation d'une cause potentielle, et aux écarts de rendement sur maind'œuvre des cinq dernières années (preuve de co‐variation). De façon générale, les résultats confirment l'ensemble des hypothèses prévoyant les effets de similitude et de co‐variation cause/événement sur les inférences causales des individus. Les conséquences de ces résultats sur la conception des systèmes d'information comptable sont examinées dans la conclusion.